(untitled) - FAO (Rome, 1996)
The book deals with management of water for agriculture. Irrigation scheduling is essential to conserve water, to improve irrigation performance and to achieve sustainability of irrogated agriculture. A substantial part of irrigation research has been devoted to the development of a range of tools and techniques in irrigation scheduling
Keywords: irrigation,water supply